Spatiotemporal variations in groundwater chemistry of a small tropical island using graphical and geochemical models - Kura, Nura Umar; Ramli, Mohammad Firuz; Sulaiman, Wan Nor Azmin; Ibrahim, Shaharin; Aris, Ahmad Zaharin; Narany, Tahoora Sheikhy (Elsevier, 2015)
In this work, the spatial and temporal variations in the groundwater chemistry of Kapas Island were assessed using geochemical and graphical models. The Durov diagram classifies the groundwater of the island into three water types; Ca- HCO3-, Na- HCO3-, and Na-Cl types with Ca- HCO3− as the dominant water type. The Schoeller diagram reveals that the order of abundance in ions was Ca2+ > Na+> K+> Mg2+, for cations and HCO3− > Cl− > SO42− for anions. These findings would help in creating a sustainable management plan through strategizing visitations and pumping periods to ensure that the island's aquifer and other smaller islands with similar characteristics are well protected